PENINGKATAN KETERAMPILAN SOSIAL MEMALUI METODE BERMAIN PERAN DRAMA PADA SISWA KELOMPOK B DI TK AISYIYAH BUSTANUL ATHFAL 58 SURABAYA - ratno abidin (Universitas Muhammadiyah Surabaya, 2016)
The problem in this research is the activity of learning in kindergarten is monotonous, as well as filling the school magazine, drawing and coloring pictures. In addition, the learning activity is still a lot of emphasis on the academic standing and often using FAQ or lectures where teachers are more active role. So the method of playing the role is still very rarely implemented. Therefore it is necessary to do some research related to the application of methods play a role to improve the social skills of children .Berdasarkan results of this study showed an increase in social skills using role play. Prior to using the method of playing the role of the social skills of children lacking some social skills, namely a lack of awareness of children to a friend, a lack of respect towards friends, share the child's lack of attitude and a lack of motivation to give his friend. After going through the three cycles visible changes that increase social skills children are expected to gradually increase the child is more concerned about a friend, a child can share with friends, children can appreciate and respect your friends and children can motivate a friend. Keywords: Role Play Methods, Social Skills